Fabrication of Nanocomposite Membrane with Nanomaterial Filler for Desalination - Muhammad Nur Alam; Indah Raya; Ahyar Ahmad; Paulina Taba; Suriati Eka Putri; Harningsih Karim (Universitas Gadjah Mada, 2024)
This review aims to provide a complete overview on the modification of polymer and biopolymer membranes into nanocomposite membrane materials. Fabrication of nanocomposite membranes is carried out by incorporating inorganic filler materials in nanoparticle sizes. Nanomaterials refer to the class of materials that consist of particulate substances with any dimension of less than 100 nm at least. The properties of nanomaterials include large specific surface area, crystalline structure, shape (that regulates most of its properties as well as their unique attributes), surface morphology, and assembling phenomena. This review primarily concentrates on the recent nanotechnology-based practices to enrich the outcomes of desalination on the footings of nanocomposites, developed practicing distinct nanomaterials. A classification for various forms of nanomaterials used for building nanocomposites has also been illustrated. Special emphasis has been given to the usage of nanocomposites constructed from several nanomaterials such as nanoparticles, nanotubes, nanoshells, nanofibers, nanocapsules, nanosheets and quantum dots, and how these nanocomposites have been utilized for desalination.